Social interaction improvement through group guidance - Sriyono, Heru; Dachmiati, Sabrina; Ambarwati, Sri (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
The objective of the study was to find out whether the group guidance services could improve students social interaction. This research uses a quantitative approach through experiment. In this study, the subjects from the study were 26 students divided into an experimental group of 13 students and control group of 13 students. Data collected by questionnaire. Data were analyzed using Wilcoxon signed-rank test. The results showed that social interaction ability of experiment class students can be improved after receiving group guidance service. As for the control class which was not given group guidance service, the result showed that the level of social interaction ability did not increase significantly. These results illustrate that social interaction can be enhanced through group guidance services.